238 SERUM ALBUMIN EARLY DECREASE IS AN INDEPENDENT PREDICTOR OF MAJOR COMPLICATIONS AFTER ONCOLOGICAL ESOPHAGECTOMY; RESULTS FROM A LARGE EUROPEAN SERIES. (17th September 2021) - Labgaa, Ismail; Mantziari, Styliani; Winiker-Seeberger, Michael; Pasquier, Jerôme; Messier, Marguerite; Elliot, Jessie A; Kamiya, Satoshi; Kalff, Marianne C; Hübner, Martin; Allemann, Pierre; Henegouwen, Mark Van Berge; Nilsen, Magnus; et al.
Abstract:  : The predictive value of postoperative albuminemia decrease (ΔAlb) has been increasingly evidenced in different types of major surgery but data on esophagectomy remain scarce. This study aimed to assess the predictive value of ΔAlb for adverse short-term outcomes after oncological esophagectomy. Methods: Retrospective analysis of an international multicentric cohort of patients undergoing oncological esophagectomy between 2006–2017. Patients with missing pre- and postoperative albumin values were excluded from the analysis. Primary endpoint was postoperative morbidity according to Clavien classification. Secondary endpoints were Comprehensive Complication Index (CCI) and length of hospital stay (LoS). Results: A total of 1046 patients were analyzed. Major complications were reported in 363 (34.7%) patients. Albuminemia showed a rapid postoperative decrease on postoperative day 1 (POD1) (ΔAlb POD1) with a median value of 11 g/L. ROC curve analysis determined a cut-off of 11 g/L for the prediction of overall complications. Patients with ΔAlb POD1 ≥ 11 g/L showed increased overall complications (p = 0.004), major complications (p = 0.009) and CCI (p = 0.006) while LoS was comparable (p = 0.099). On multivariable analysis, ΔAlb POD1 ≥ 11 g/L was an independent predictor of overall (OR: 1.55; 95% CI 1.09–2.21; p = 0.015) and major complications (OR: 1.43; 95% CI 1.09–1.89; p = 0.009). Conclusion: Oncological esophagectomy induced a rapid decrease of albuminemia. ΔAlb POD1 ≥ 11 g/L was independently associated with the occurrence of overall and major postoperative complications. ΔAlb appears as a promising biomarker to detect patients at risk of adverse outcomes after oncological esophagectomy.